A) 4 (y + 3) = — 8; в) (х) = 36; б) 4х-7 = -3; г) (х-4) = 6

A) 4 (y + 3) = - 8; в) (х) = 36; б) 4х-7 = -3; г) (х-4) = 6

  • А) 4у + 12 = -8
    4у = -20
    у = -5
    в) якщо я правильно зрозуміла, то тут по модулю
    х = + 36
    х = -36
    б) 4х = 4
    х = 1
    г) якщо я правильно зрозуміла, то тут теж по модулю
    х = -2
    х = 10
  • A) 4 (y + 3) = - 8
    4у + 12 = -8
    4у = -8-12
    4у = -20
    у = -20 / 4 = -5

    в) х = 36
    х1 = 36
    x2 = -36

    б) 4х-7 = -3
    4х = -3 + 7
    4х = 4
    х = 4/4 = 1

    г) х-4 = 6
    х-4 = 6
    х1 = 6 + 4 = 10

    х-4 = -6
    х2 = -6 + 4 = -2

Понравилась статья? Поделиться с друзьями:
Добавить комментарий

18 + = 23

;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!: